2013
DOI: 10.2106/jbjs.l.00819
|View full text |Cite
|
Sign up to set email alerts
|

Guiding Femoral Rotational Growth in an Animal Model

Abstract: Guided growth using plates may be effective for correction of rotational and multiplanar deformities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 19 publications
0
41
0
1
Order By: Relevance
“…Arami et al. ( 2013 ) reported that the additional deformity was one of the limitations of their study. Thus, insertion of these plates with the greatest possible angle to the long axis will lead to both greater rotation and safe controlled growth.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Arami et al. ( 2013 ) reported that the additional deformity was one of the limitations of their study. Thus, insertion of these plates with the greatest possible angle to the long axis will lead to both greater rotation and safe controlled growth.…”
Section: Discussionmentioning
confidence: 89%
“…There has been one previous study on the rotationally guided growth of the femur (Arami et al. 2013 ). These authors used the distal femur in rabbits, and in order to create an external rotation, they placed the plates in appropriate positions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In der Wachstumslenkung gibt es Hinweise dafür, dass auch Rotationsdeformitäten korrigiert werden können. Arami und Mitarbeiter bewiesen in einem Hasenmodell, dass 2 schräg angebrachte Platten medial und lateral das axiale Rotationswachstum am distalen Femur beeinflussen [70].…”
Section: Perspektivenunclassified